Self-Efficacy, State Anxiety, and Motivation during Mandatory Combative Training - Hector R. Morales-Negron; Robert C. Eklund; Gershon Tenenbaum (Pamukkale University, 2011)
U.S. Army soldiers (n = 52) attending Instructor Combative Training (ICT) courses at two military installations in the US were examined before, during and at the end of the course on self-defense efficacy (SDE), teaching combatives self-efficacy (TCSE), combatives state anxiety (CSA), and motivation. In a quasi-experimental design, a cognitive-behavioral coping intervention targeting combative anxiety was implemented. Two classes (n = 32) constituted the interventions and one class as a control group (n = 20). RM ANOVAs revealed a significant increase in SDE and TCSE across the course for the experimental groups. Specifically, the intervention group soldiers scored lower in CSA during high anxiety driven events and higher in motivation than the control group soldiers along the course progression. The results provide preliminary evidence that a combatives anxiety coping strategy can influence SDE, TCSE, CSA, and motivation during mandatory psychologically demanding training.